Pembuatan Prototipe Kursi Roda Inovatif Dengan Akses Suara Menggunakan Smartphone Berbasis Mikrokontroler ATMega 8A - Prasetio, Akbar (P3M Politeknik Negeri Medan, 2021)
This low power consumption microcontroller is able to execute instructions with a maximum speed of 16MIPS at a frequency of 16MHz and the ATmega8 is tested to work at a voltage between 4.5 - 5.5 V. Test results of motor drivers 1 and 2 working at a voltage of 4.99 prove that the driver circuit has worked according to its function, namely controlling the motor in 2 directions according to the input given. Motor speed can be controlled by adjusting the motor voltage, the higher the voltage, the faster the motor rotates. The voltage drop will slow down the motor to the desired speed, The sensor response if it encounters an obstacle in front of the wheelchair will stop 10 cm before hitting the object. Then the load test is added gradually from 0 to 451 grams. The wheelchair will appear to be starting to slow down at its maximum weight, making it less responsive to commands. After testing, it can be concluded that the tool works as desired, namely controlling the motion of the wheelchair with voice commands and it can be declared successful although there are still some weaknesses and shortcomings that must be improved.